Systemic Acquired Resistance and Induced Systemic Resistance in Conventional Agriculture - Vallada, G.E.; Goodman, R.M.
Plants possess a range of defenses that can be actively expressed in response to pathogens and parasites of various scales, ranging from microscopic viruses to insect herbivores. The timing of these defense responses is critical and can be the difference between being able to cope or succumbing to the challenge of a pathogen or parasite. Systemic acquired resistance (SAR)and induced systemic resistance (ISR)are two forms of induced resistance; in both SAR and ISR, plant defenses are preconditioned by prior infection or treatment that results in resistance (or tolerance)against subsequent challenge by a pathogen or parasite. Great strides have been made over the past 20 yr in understanding the physiological and biochemical basis of SAR and ISR. Much of this knowledge is due to the identification of a number of chemical and biological elicitors, some of which are commercially available for use in conventional agriculture. However, the effectiveness of these elicitors to induce SAR and ISR as a practical means to control various plant diseases is just being realized. In this review, we first briefly summarize the fundamentals of ISR and SAR, for which a number of critical reviews already exist. We then examine the efficacy of SAR and ISR in published field-based studies. We place special emphasis on the benefits, drawbacks, and future considerations for the improved use of chemical and biological elicitors of induced resistance in conventional agriculture; this includes the potential to exploit genetic variability within populations of crop species to improve the utility of SAR and ISR in the field.